Ambulatory Surgery for Perianal Crohn’s Disease: Study of Feasibility - S. Sibio; A. Di Giorgio; M. Campanelli; S. Di Carlo; A. Divizia; C. Fiorani; R. Scaramuzzo; C. Arcudi; G. Del Vecchio Blanco; L. Biancone; G. Sica (Gastroenterology Research and Practice)
Background. One-third of Crohn’s disease (CD) patients present perianal fistula. The gold standard in the diagnosis and treatment of symptomatic perianal disease (PAD) in CD is the exploration of the anal canal and distal rectum under anesthesia (EUA). This procedure is mainly conducted as a day case surgery. Unfortunately, it is not always possible to proceed within the ideal timing and any delay may well represent a relevant clinical issue. The aim of this study was to evaluate the feasibility of outpatient treatment of symptomatic perianal fistulas in CD patients. Methods. All CD patients under regular follow-up at our inflammatory bowel disease referral center, presenting with symptomatic perianal fistulas, were offered surgical consultation. The data of patients were prospectively collected for three years (February 2014 to February 2017) for the purpose of the study. All clinical information, including previous EUA and/or records from MRI and endoscopic ultrasound, was included. Outpatient anal canal and distal rectum exploration and treatment (OE) were undertaken during the specialist surgical consultation. Fistulas were classified according to Parks’s classification; the type of outpatient treatment and compliance of patients were recorded. Pain was assessed by VAS at the time of the procedure and during the first control. Patients were followed up in the surgical clinic in relation to the study. Results. Ninety-two CD patients with symptomatic perianal fistulas had surgical consultation during the study period. OE was offered to all but 18 patients who fulfilled the exclusion criteria or had an extremely severe disease; six patients refused the OE (8.11%). Of the 68 patients undergoing OE, eleven (16.18%) had previous surgery for perianal disease. The OE was accomplished in sixty-one patients (89.71%), while in 7 patients, it was abandoned for scarce compliance. Nine patients (14.75%) underwent drainage of perianal abscess; in 3 of them, it was possible to probe the fistula tract, find the internal orifice, and pass a loose seton. Overall, setonage was performed in 50 patients (81.97%). Rectovaginal setons were placed in 3 patients and more than one seton (up to 3) in 6 cases. Fistulotomy was performed in 4 simple subcutaneous fistulous tracts. Concordance with the preoperative findings was found in 54 out of 61 patients. EUA was scheduled at the time of OE for the 7 patients who did not complete the procedure. All sixty-one patients who had the OE were followed up for a minimum of 12 months. Conclusions. This preliminary study indicates that OE in CD patients with symptomatic perianal fistulas is safe and feasible in a high-volume referral center. It might provide several benefits, including patients’ logistics, reduce or remove patients’ symptoms and discomfort, allow for a timely start of medical therapy, and avoid further complications.